Occlusion of Bilobulated Left Atrial Appendage Using the Dual-Watchman Technique: A Long-Term Follow-Up Study - Chen, Tao; Wang, Qing-song; Liu, Ge; Lu, Xu; Song, Ting-ting; Shi, Ming-yuan; Zhu, Hang; Mu, Yang; Guo, Jun; Chen, Yun-dai (Frontiers in Cardiovascular Medicine, 2022)
Background: Percutaneous left atrial appendage (LAA) occlusion has been considered an efficient alternative of oral anticoagulation to prevent embolic events in patients with non-valvular atrial fibrillation (NVAF). Due to the complexities and heterogeneous anatomy of LAA structure, the single device approach may not always fit big bilobulated LAA. The aim of this study was to evaluate the feasibility and safety of one-stop implantation of dual Watchman for patients with bilobulated LAA. Methods: Between December 2015 and December 2021, patients who underwent the complete closure of LAA with dual Watchman devices were identified and included in the analysis. The anatomic morphology, procedure characteristics, procedure safety and procedural complication were analyzed. Cardiac CT or transesophageal ultrasound were obtained 7 days, 6 months, 1 year, and 2 years postoperatively to evaluate the effect of occlusion. Results: Among 330 patients who underwent LAA occlusion during the study period, 7 (2.1%) patients were occluded with one-stop implantation of double Watchman strategy. Successful occlusion was achieved in all patients. 1 patient was used the double access sheath strategy, and 6 patients used only single access sheath. Pericardial effusion occurred in one case during the 7-day perioperative period. There were no device embolization, thrombosis or obvious peri-device leakage (≥5mm) during the 2-year follow-up, except for two cases with a 2mm of incomplete LAA sealing. Conclusions: The one-stop implantation of dual Watchman is feasible and safe, which might provide a strategy to occlude big bilobulated LAA when an incomplete closure is inevitable with a single device.